Potential of Monoclonal Antibody (mAb) as Alternative Treatment of Alzheimer: A Sytematic Scoping Review - Armansyah, Nuraulia Aghnia; Putri, Azalia Melati; Azizah, Wafiq Nurul; Maryati, Ida (Jurnal Pendidikan Keperawatan Indonesia, 2023)
Alzheimer's disease (AD) is a global problem that is expected to increase along with the increasing rate of population aging. Monoclonal antibodies (mAb) are considered capable of overcoming the accumulation of amyloid-β plaques; pathological signs of AD. This study aims to explore the potential of mAbs as alternative pharmacological therapies for the elderly with AD. This study uses a scoping review design based on the PAGER framework. The results of the study were identified based on the PRISMA-ScR protocol and criticized using the JBI Critical Appraisal Checklist. Article searches were conducted through 3 databases including EBSCO-Host Academic Science Complete, PubMed, and ScienceDirect, and 3 online resources including Sage Journals, Taylor Francis, and Google Scholar. Inclusion criteria were full English text, primary research articles, and published between 2018-2022.A total of 8 articles were included in the review. Most of the evidence shows 6 mAbs have potential to reduce amyloid-β accumulation in AD patients. Alternative therapy with monoclonal antibodies has side effects that represent a major problem in the high incidence of vasogenic cerebral edema and micro cerebral hemorrhage or Amyloid Related Imaging Abnormalities (ARIA). Plasma tau has the potential to strengthen the clinical diagnosis of AD. The use of mAbs as AD immunotherapy can reduce amyloid-β with side effects that are monitored continuously. Differences in mAb examination results can be influenced by less accurate clinical diagnostic accuracy.